2017
DOI: 10.1248/bpb.b17-00010
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine Promotes S-Phase Arrest and Inhibits Cell Proliferation of Human Breast Cancer Cells <i>in Vitro</i> through Mitochondria-Mediated Apoptosis

Abstract: Breast cancer is one of the most lethal malignancies in the world. Oxymatrine is the major effective and toxic alkaloid component which is derived from the root of Sophora flavescens AIT, a traditional Chinese medicine which is widely distributed in Asia and the Pacific Islands. In the current research study, we investigated the effects and mechanisms of action of oxymatrine on breast cancer cells. We demonstrated that the viability and single cell proliferation capability of MCF-7 and MDA-MB-231, two breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…The B-cell/leukemia-2 (Bcl-2), cleaved PARP and caspase-3 proteins were reported as the key proteins in regulating cell apoptosis. Decreased Bcl-2 or increased cleaved PARP and caspase-3 will promote cell apoptosis (27). In the present study, we found that lenalidomide and cisplatin induces caspases-3 activity and cleaved PARP expression, while reduces Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 59%
“…The B-cell/leukemia-2 (Bcl-2), cleaved PARP and caspase-3 proteins were reported as the key proteins in regulating cell apoptosis. Decreased Bcl-2 or increased cleaved PARP and caspase-3 will promote cell apoptosis (27). In the present study, we found that lenalidomide and cisplatin induces caspases-3 activity and cleaved PARP expression, while reduces Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 59%
“…Equol, which is a metabolite of daidzein, induces apoptosis in SMMC-7721 human hepatocellular carcinoma cells through the intrinsic and endoplasmic reticulum stress pathways (26). Caspase-9 and the Bcl-2/Bax ratio are commonly used activity markers of the mitochondrial apoptotic pathway (43)(44)(45). In the present study, western blotting was used to detect these markers, revealing that the cleavage of caspase-9 increased and the ratio of Bcl-2/Bax decreased in both cell lines in a dose-dependent manner, which indicated that daidzein-induced apoptosis was mediated via the mitochondrial apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Oxymatrine (OMT) is an alkaloid derived from extract of Sophora flavescens and Sophora alopecuroides, which is a traditional Chinese medicine with anti-tumor [ 8 , 9 ], anti-inflammatory [ 10 ], and attenuating heart failure properties [ 11 ]. OMT is widely applied for various human diseases such as hepatitis B infection and liver fibrosis [ 12 ], and provides protection from damage to the liver, intestines, and heart [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%